Premedication with intranasal dexmedetomidine in patients undergoing total knee arthroplasty under spinal anaesthesia (TKADEX)—a prospective, double-blinded, randomised controlled trial - Tiainen, Suvi-Maria; Heinonen, Heta; Koskinen, Atte; Mäkelä, Sanna; Laitio, Ruut; Löyttyniemi, Eliisa; Mäkelä, Keijo; Saari, Teijo I.; Uusalo, Panu (Elsevier BV, 2025)
Background
Previous studies have shown that perioperative use of adjuvants, such as the alpha-2 agonist dexmedetomidine, may reduce postoperative pain and opioid requirements. However, information about optimal dosing is lacking. We investigated if premedication with intranasal dexmedetomidine compared with placebo reduces postoperative pain in patients undergoing total knee arthroplasty under spinal anaesthesia.
Methods
This single-centre, double-blind, two-arm study compared premedication with intranasal dexmedetomidine (single 1 μg kg−1 dose) to intranasal saline in 101 consecutive elective patients undergoing total knee arthroplasty under spinal anaesthesia. The primary outcome was postoperative pain measured with the numerical rating scale during the first 24 h. Secondary outcomes were postoperative opioid requirement, perioperative haemodynamic variables, requirement of additional intraoperative sedation, incidence of postoperative nausea and vomiting, and patient satisfaction at 30 days after surgery.
Results
Patients in the dexmedetomidine group had lower numerical rating scale scores [median (interquartile range) 2.0 (0.0–3.0)] at 3 h when compared with the control group [3.0 (2.0–4.0)] (P=0.037). Cumulative 24 h opioid requirements (in morphine equivalents) did not differ between dexmedetomidine [45 mg (30–68 mg)] and control groups [53 mg (38–88 mg)] (P=0.334). More patients in the dexmedetomidine group were satisfied with pain management in the ward (P=0.0013). The groups did not differ in the incidence of postoperative nausea and vomiting (P=0.310) or haemodynamic adverse events (P>0.27 for all).
Conclusions
Our results indicate that intranasal dexmedetomidine may reduce postoperative pain and the requirement for additional sedation and increase short-term patient satisfaction in patients undergoing total knee arthroplasty.